Enzyme supplementation in nutritionally reduced diets for piglets in the early-nursery phase - de Medeiros, Cícero Jorge; Pascoal, Leonardo Augusto Fonseca; Costa e Silva, Luiz Fernando; Guerra, Ricardo Romão; Watanabe, Pedro Henrique; Givisiez, Patrícia Emília Naves; Almeida, Jorge Luiz Santos de; da Silva, Wilson Araújo; Silva, Mekiciene de Brito; de Azevedo, Mirian Lima; Rocha, Gustavo Fideles; Soares, Pierre Castro (Frontiers in Animal Science, 2026)
Optimization of nutrient utilization in weaned piglets, aiming for greater feed efficiency and lower excretion, is a key focus in animal production. Among the strategies, enzyme supplementation stands out. The study evaluated the use of an enzyme complex in diets with reduced nutritional and energy levels for piglets in the nursery phase. Forty piglets weaned at 26 days old, with an initial average weight of 7.85 ± 1.27 kg, were used. The animals were distributed in a randomized block design, in a 2×2 factorial arrangement: with or without nutritional reduction and with or without enzyme supplementation. The complex contained phytase (1500 U/g) and xylanase (350 U/g). There was no interaction between factors for performance (P > 0.05). Nutritional reduction increased feed intake (P = 0.018) and worsened feed conversion (P = 0.024) in Period II, and in Period III it reduced weight gain (P = 0.032) and further worsened feed conversion (P = 0.026). Enzyme supplementation improved weight gain (P = 0.012) and feed conversion (P = 0.050) in Period III. The reduced diet resulted in a lower incidence of diarrhea (P < 0.002). Nutritional reduction decreased ash and phosphorus digestibility, whereas enzyme supplementation improved NDF (P = 0.021) and ADF digestibility (P = 0.014). The combination of nutritional reduction and enzyme supplementation reduced the relative weights of the liver (P = 0.027) and pancreas (P < 0.0001). Nutritional reduction impaired intestinal morphometry, reducing villus height (P = 0.002) and crypt depth (P = 0.037). Enzyme supplementation increased crypt depth (P = 0.018) and reduced the villus height-to-crypt depth ratio (P = 0.005). Additionally, it increased the expression of NaPi-IIb (P = 0.050), SGLT-1 (P = 0.015), and PEPT-1 (P = 0.018) transporters. It is concluded that nutritional reduction negatively affected the piglets, and although supplementation with the enzyme complex did not fully neutralize the nutritional challenge, it was effective in improving the digestibility of the fibrous fraction and increasing gene expression of nutrient transporters.